Method for preparing lithium orthosilicate and lithium carbonate from waste lithium batteries

By using transient high-temperature heating technology to stimulate the reaction between lithium vapor and silicon dioxide in the cathode material powder of waste lithium batteries, lithium orthosilicate is generated and transition metal elements are reduced. This solves the problems of high energy consumption and complex process in waste lithium battery recycling, and realizes efficient and environmentally friendly full-quantity recycling of lithium metal.

CN120943266APending Publication Date: 2025-11-14TSINGHUA UNIVERSITY
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202511010873.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-11-14

AI Technical Summary

Technical Problem

Existing technologies for recycling waste lithium batteries suffer from high energy consumption, high costs, and serious environmental pollution. Furthermore, traditional methods require complex preparation processes and high-temperature operations, making it difficult to achieve rapid conversion and full-scale recycling of lithium metal.

Method used

By employing transient high-temperature heating technology, waste lithium battery cathode material powder and silicon dioxide sheets are stacked together. Through pulse heating treatment, the gas-phase volatilization of lattice lithium is stimulated, realizing the rapid gas-solid phase synthesis of lithium orthosilicate. The lithium vapor reacts with silicon dioxide to generate lithium orthosilicate, while the transition metal oxide is reduced to elemental form, simplifying the process flow.

Benefits of technology

It enables rapid conversion and full-scale recycling of lithium metal from waste lithium batteries, reducing energy consumption and environmental impact, improving recycling efficiency, simplifying the process, and making it suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120943266A_ABST
    Figure CN120943266A_ABST
Patent Text Reader

Abstract

The invention discloses lithium orthosilicate, a preparation method and application thereof and a preparation method of lithium carbonate, and the preparation method of the lithium orthosilicate comprises the following steps: carrying out discharge treatment and pretreatment on a waste lithium battery to obtain waste positive electrode material powder; pressing the waste positive electrode material powder into a positive electrode material sheet; the positive electrode material sheet and a silicon dioxide sheet are stacked in an electric heating graphite boat, and the silicon dioxide sheet is located on the side, away from the electric heating graphite boat, of the positive electrode material sheet; the electric heating graphite boat is subjected to pulse heating treatment, the temperature of the pulse heating treatment ranges from 800 DEG C to 1000 DEG C, and the lithium orthosilicate is obtained. The transient high-temperature heating technology is adopted to excite gas-phase volatilization of lattice lithium in the waste lithium battery positive electrode material powder, and volatile lithium steam is directly used as a gas-phase reactant, so that gas-solid-phase rapid synthesis preparation of lithium orthosilicate is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of waste lithium battery resource recycling, specifically to lithium orthosilicate and its preparation methods and applications, and methods for preparing lithium carbonate. Background Technology

[0002] With the rapid development of the electric vehicle industry, the large-scale recycling of waste lithium batteries faces severe challenges, and the total amount of waste lithium-ion batteries worldwide is gradually increasing. While traditional pyrometallurgical and hydrometallurgical recycling technologies can achieve a battery metal recovery rate of over 95%, they suffer from high energy consumption, high costs, and severe environmental pollution. Meanwhile, the demand for efficient carbon capture technology is increasingly urgent, and the low cost and high performance of adsorbents have become key bottlenecks. Lithium orthosilicate has a theoretical CO2 adsorption capacity of 367 mg / g, and its adsorption temperature range is approximately 500℃ to 700℃, making it considered an ideal adsorbent for absorbing CO2 from high-temperature industrial flue gas. Utilizing waste lithium-ion battery cathode materials to replace ore for lithium extraction offers both economic and environmental benefits. However, current preparation technologies using waste lithium battery cathode materials as a lithium source typically require complex recycled lithium carbonate preparation processes such as reduction roasting, hydrometallurgical lithium extraction, and evaporation crystallization. Furthermore, the process requires mixing recycled lithium carbonate and silicon dioxide under high-temperature (350℃ to 900℃) conditions and then undergoing solid-state sintering for several hours, resulting in energy-intensive and lengthy processes.

[0003] Therefore, there is a need for a short-process, high-efficiency, and environmentally friendly transient high-temperature thermal treatment recycling technology to achieve rapid conversion of lithium metal in waste lithium battery cathode materials into environmentally functional materials, and simultaneously realize the full-scale recycling of waste lithium battery metal.

[0004] It should be noted that the above statements are only used to provide background information related to this application and do not necessarily constitute prior art. Summary of the Invention

[0005] In a first aspect, this application proposes a method for preparing lithium orthosilicate, comprising: discharging and pretreating waste lithium batteries to obtain waste cathode material powder; pressing the waste cathode material powder into cathode material sheets; stacking the cathode material sheets and silicon dioxide sheets in an electrothermal graphite boat, wherein the silicon dioxide sheets are located on the side of the cathode material sheets away from the electrothermal graphite boat; and subjecting the electrothermal graphite boat to pulse heating treatment at a temperature of 800℃~1000℃ to obtain the lithium orthosilicate. This application employs transient high-temperature heating technology to excite the vapor-phase volatilization of lattice lithium in the waste lithium battery cathode material powder and directly utilizes the volatilized lithium vapor as a gas-phase reactant, achieving rapid gas-solid phase synthesis of lithium orthosilicate.

[0006] In addition, the preparation method according to the above embodiments of this application may also have the following additional technical features:

[0007] In some embodiments of this application, the waste lithium batteries include at least one of nickel-cobalt-manganese ternary lithium batteries and lithium cobalt oxide batteries; wherein the positive electrode active material of the nickel-cobalt-manganese ternary lithium battery includes LiNi. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.7 Co 0.2 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 At least one of O2. Therefore, waste lithium batteries are widely available and have low costs, which is conducive to improving the recycling efficiency of waste lithium batteries. Moreover, the transition metal elements formed after delithiation can be used as raw materials for various reactions, and have high utilization value.

[0008] In some embodiments of this application, the method for preparing the silicon dioxide wafer includes: pressing silicon dioxide powder into a silicon dioxide wafer; wherein the specific surface area of ​​the silicon dioxide powder is 100 m². 2 / g~400m 2 / g. Therefore, the high porosity of silica powder is conducive to the permeation of lithium vapor, thereby improving the synthesis kinetics of lithium orthosilicate.

[0009] In some embodiments of this application, the mass ratio of the positive electrode material sheet to the silicon dioxide sheet is 1:(0.05-0.2). This facilitates a more complete reaction, reduces raw material waste, and thereby improves the synthesis yield of lithium orthosilicate.

[0010] In some embodiments of this application, the pulse current of the pulse heating treatment is 100A to 140A, and the pulse duration is 8min to 14min. Therefore, the heating time is short, which can reduce the thermal volatilization loss of lithium metal in the cathode material sheet.

[0011] In some embodiments of this application, the pretreatment includes: mechanically crushing the waste lithium batteries after discharge treatment to obtain crushed waste; vibrating sieving of the crushed waste to obtain lithium battery black powder; and foam flotation of the lithium battery black powder to obtain the waste cathode material powder. This facilitates the removal of impurities from the waste cathode material powder.

[0012] In a second aspect, this application proposes the application of lithium orthosilicate in carbon dioxide adsorption, wherein the lithium orthosilicate is prepared using the method described in the first aspect of this application. This facilitates the high-value recycling of waste lithium batteries.

[0013] In a third aspect, this application proposes a method for preparing lithium carbonate, comprising: discharging and pretreating waste lithium batteries to obtain waste cathode material powder; pressing the waste cathode material powder into cathode material sheets; placing the cathode material sheets and silicon dioxide sheets in an electrothermal graphite boat, wherein the silicon dioxide sheets are located on the side of the cathode material sheets away from the electrothermal graphite boat; subjecting the electrothermal graphite boat to pulse heating treatment at a temperature of 800℃~1000℃ to obtain lithium-rich transition metal powder; leaching the lithium-rich transition metal powder to obtain transition metal elements and a lithium-rich solution; mixing the lithium-rich solution with sodium carbonate and evaporating and concentrating it to obtain the lithium carbonate. This application employs transient high-temperature heating technology to enrich residual lithium in waste lithium battery cathode material powder and reduce high-valence transition metal oxides to transition metal elements, thereby improving the efficiency of full-quantity recovery of battery metals. Furthermore, the process is simple, environmentally friendly, and easily scalable for industrial production.

[0014] In some embodiments of this application, the leaching process includes mixing the lithium-rich transition metal powder with water, wherein the mass ratio of water to the lithium-rich transition metal powder is (5-20):1. This reduces raw material waste and improves the leaching rate of the transition metal element.

[0015] In some embodiments of this application, the leaching treatment time is 10s to 60s, and the leaching treatment temperature is 20℃ to 50℃. This is beneficial for improving the leaching rate of transition metal elements. Attached Figure Description

[0016] The above and / or additional aspects and advantages of this application will become apparent and readily understood from the description of the embodiments taken in conjunction with the following drawings, in which:

[0017] Figure 1 This is a process flow diagram of the preparation of lithium orthosilicate and lithium carbonate according to an embodiment of this application. Detailed Implementation

[0018] The embodiments of this application are described in detail below, with examples of these embodiments shown in the accompanying drawings. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repetitive descriptions of practically identical structures may be omitted. This is to avoid unnecessarily lengthy descriptions and to facilitate understanding by those skilled in the art. Furthermore, the accompanying drawings and the following description are provided to enable those skilled in the art to fully understand this application and are not intended to limit the subject matter of the claims.

[0019] Unless otherwise defined, all technical and scientific terms used in this application have the same meaning as commonly understood by one of ordinary skill in the art to which this application pertains; the terminology used in this application is for the purpose of describing particular embodiments only and is not intended to limit this application; unless otherwise stated, the values ​​of the parameters mentioned in this application can be measured using various measurement methods commonly used in the art (e.g., they can be tested according to the methods given in the embodiments of this application).

[0020] The terms “comprising” and “having”, and any variations thereof, in the specification and claims of this application are open-ended expressions, meaning they include what is specified in this application but do not exclude other aspects.

[0021] In the description of this application, all figures disclosed herein, whether or not the words "approximately" or "about" are used, are approximate values. Each figure may vary by less than 10% or by a difference that is considered reasonable by one of the art, such as 1%, 2%, 3%, 4%, or 5%.

[0022] The "range" disclosed in this application is defined by a lower limit and an upper limit. A given range is defined by selecting a lower limit and an upper limit, which define the boundaries of a particular range. Ranges defined in this way can include or exclude endpoints and can be arbitrarily combined; that is, any lower limit can be combined with any upper limit to form a range. For example, if ranges of 60–120 and 80–110 are listed for a specific parameter, it is understood that ranges of 60–110 and 80–120 are also expected. Furthermore, if minimum range values ​​of 1 and 2 are listed, and if maximum range values ​​of 3, 4, and 5 are listed, then the following ranges are all expected: 1–3, 1–4, 1–5, 2–3, 2–4, and 2–5. In this application, unless otherwise stated, the numerical range "a–b" represents a shortened representation of any combination of real numbers between a and b, where a and b are real numbers. For example, the numerical range "0~5" indicates that all real numbers between "0" and "5" have been listed in this article; "0~5" is simply a shortened representation of these numerical combinations. Furthermore, when a parameter is stated as an integer ≥2, it is equivalent to disclosing that the parameter is, for example, an integer such as 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0023] In this application, the order in which the steps are written does not imply a strict execution order and does not limit the implementation process. The specific execution order of each step should be determined by its function and possible internal logic. Unless otherwise specified, all steps in this application can be performed sequentially or randomly, preferably sequentially. For example, if the method includes steps (a) and (b), it means that the method may include steps (a) and (b) performed sequentially, or it may include steps (b) and (a) performed sequentially. For example, if the method may also include step (c), it means that step (c) can be added to the method in any order. For example, the method may include steps (a), (b), and (c), or it may include steps (a), (c), and (b), or it may include steps (c), (a), and (b), etc.

[0024] Unless otherwise specified, all embodiments and optional embodiments of this application can be combined to form new technical solutions.

[0025] Unless otherwise specified, all technical features and optional technical features of this application may be combined to form new technical solutions.

[0026] In a first aspect of this application, a method for preparing lithium orthosilicate is proposed, comprising:

[0027] S1: Discharge and pre-treat the waste lithium batteries to obtain waste cathode material powder.

[0028] In some embodiments of this application, the waste lithium batteries include at least one of nickel-cobalt-manganese ternary lithium batteries and lithium cobalt oxide batteries; wherein, the positive electrode active material of the nickel-cobalt-manganese ternary lithium battery includes LiNi. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.7 Co 0.2 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 At least one of O2. Therefore, waste lithium batteries are widely available and have low costs, which is conducive to improving the recycling efficiency of waste lithium batteries. Moreover, the transition metal elements formed after delithiation can be used as raw materials for various reactions, and have high utilization value.

[0029] In some embodiments of this application, the discharge treatment includes: placing the waste lithium battery in NaCl brine and soaking it for 20 hours to fully discharge it, thereby reducing safety hazards such as combustion and explosion during the mechanical crushing process.

[0030] In some embodiments of this application, the pretreatment includes: mechanically crushing the waste lithium batteries after discharge treatment to obtain crushed waste; vibrating sieving of the crushed waste to obtain lithium battery black powder; and foam flotation of the lithium battery black powder to obtain waste cathode material powder. This facilitates the removal of impurities from the waste cathode material powder.

[0031] Specifically, the waste lithium batteries after discharge treatment can be placed in a vacuum drying oven and dried at 80°C. Then, the waste lithium batteries are mechanically crushed to obtain crushed waste. The crushed waste is placed in a vibrating screen for oscillation and separation to obtain copper-aluminum current collectors and plastics on the screen, and lithium battery black powder on the undersize. The lithium battery black powder is placed in a foam flotation machine for flotation separation to obtain waste positive electrode material powder and waste graphite negative electrode.

[0032] It is understandable that the waste cathode material powder contains about 3 wt.% polyvinylidene fluoride binder, and its presence has a negligible impact on the carbon fixation ability of the obtained lithium orthosilicate.

[0033] S2: Press waste cathode material powder into cathode material sheets.

[0034] Specifically, waste cathode material powder can be pressed under a pressure of 15 MPa for 20 seconds to obtain cathode material sheets.

[0035] S3: The positive electrode material sheet and the silicon dioxide sheet are stacked in an electrothermal graphite boat, wherein the silicon dioxide sheet is located on the side of the positive electrode material sheet away from the electrothermal graphite boat.

[0036] It should be noted that the silicon dioxide sheet must be stacked on top of the positive electrode material sheet. This process utilizes transient high temperature to volatilize the lithium-containing components in the bottom positive electrode material sheet upwards, allowing the lithium vapor to react with the upper silicon dioxide sheet in a gas-solid phase reaction to form lithium orthosilicate. When the positive electrode material sheet is stacked on top of the silicon dioxide sheet, the lithium vapor released from the positive electrode material sheet will bypass the silicon dioxide sheet and be directly emitted into the environment, failing to achieve sufficient contact with the silicon dioxide sheet, thus hindering the synthesis of lithium orthosilicate.

[0037] In some embodiments of this application, the mass ratio of the positive electrode material sheet to the silicon dioxide sheet is 1:(0.05~0.2), for example, it can be 1:0.05, 1:0.08, 1:0.1, 1:0.13, 1:0.15, 1:0.18, or 1:0.2. This facilitates a more complete reaction, reduces raw material waste, and thus improves the synthesis yield of lithium orthosilicate.

[0038] In some embodiments of this application, the method for preparing silicon dioxide wafers includes: pressing silicon dioxide powder into silicon dioxide wafers, specifically, pressing the silicon dioxide powder under a pressure of 15 MPa for 20 seconds to obtain silicon dioxide wafers; wherein, the specific surface area of ​​the silicon dioxide powder is 100 m². 2 / g~400m 2 / g, for example, can be 150m 2 / g、200m 2 / g、250m 2 / g、300m 2 / g, 350m 2 / g or 400m 2 / g etc. Therefore, the high porosity of silica powder is conducive to the permeation of lithium vapor, thereby improving the synthesis kinetics of lithium orthosilicate.

[0039] S4: The electrothermal graphite boat is subjected to pulse heating treatment at a temperature of 800℃~1000℃ to obtain lithium orthosilicate. Within this temperature range, the formation of lithium orthosilicate is optimal; if the temperature continues to rise, the lithium orthosilicate will melt.

[0040] Pulse heating treatment, also known as transient high-temperature heating technology, utilizes pulsed current to rapidly heat a low-resistance electrothermal graphite boat, reaching a specified high-temperature heating temperature within seconds. Specifically, a power supply's positive and negative terminals are connected to both sides of the electrothermal graphite boat, and a pulsed current is applied. According to Joule's law, the electrical energy output from the external power supply is almost entirely converted into the heat energy of the electrothermal graphite boat itself. By adjusting the magnitude and duration of the pulsed current, the transient high-temperature heating temperature of the waste positive electrode material powder and silicon dioxide powder can be controlled.

[0041] In this application, based on the differences in saturated vapor pressure of lithium, nickel, cobalt, and manganese in waste lithium batteries, a transient high temperature of 800℃ to 1000℃ is used to volatilize and separate lattice lithium from the original crystal lattice in waste cathode materials, forming lithium oxide vapor. Subsequently, the lithium oxide vapor directly reacts with silicon dioxide in a high-temperature induced gas-solid phase synthesis reaction to generate lithium orthosilicate adsorbent material. Simultaneously, transition metal oxides undergo an oxygen-loss reduction reaction under transient high-temperature induction, transforming into elemental transition metals. This improves the thermodynamic and kinetic trends of the transition metal acid leaching system and reduces the operational requirements of the acid leaching extraction process for transition metals. This application achieves significant improvements in process energy consumption, process flow, carbon emissions, and economic benefits.

[0042] In some embodiments of this application, the pulse current of the pulse heating treatment is 100A to 140A, for example, 100A, 110A, 120A, 130A, or 140A; the pulse duration is 8min to 14min, for example, 8min, 9min, 10min, 11min, 12min, 13min, or 14min. Therefore, the heating time is short, which can reduce the thermal volatilization loss of lithium metal in the positive electrode material sheet.

[0043] In a second aspect of this application, an application of lithium orthosilicate in carbon dioxide adsorption is proposed, wherein the lithium orthosilicate is prepared using the method described in the first aspect of this application. This facilitates the high-value recycling and reuse of waste lithium batteries.

[0044] In a third aspect, this application proposes a method for preparing lithium carbonate, comprising:

[0045] S10: Discharge and pre-treat the waste lithium batteries to obtain waste cathode material powder.

[0046] S20: Press waste cathode material powder into cathode material sheets.

[0047] S30: Place the positive electrode material sheet and the silicon dioxide sheet in an electrothermal graphite boat, wherein the silicon dioxide sheet is located on the side of the positive electrode material sheet away from the electrothermal graphite boat.

[0048] S40: The electrothermal graphite boat is subjected to pulse heating treatment at a temperature of 800℃~1000℃ to obtain lithium-rich transition metal powder.

[0049] It is understood that the operation process of steps S10 to S40 can refer to the preparation method of lithium orthosilicate described above, and will not be repeated here.

[0050] S50: Leach lithium-rich transition metal powder to obtain elemental transition metal and lithium-rich solution.

[0051] In some embodiments of this application, the leaching process includes mixing lithium-rich transition metal powder with water, wherein the mass ratio of water to lithium-rich transition metal powder is (5-20):1, for example, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 12:1, 14:1, 16:1, 18:1, or 20:1. This reduces raw material waste and improves the leaching rate of the transition metal.

[0052] In some embodiments of this application, the leaching time is 10s to 60s, for example, 10s, 20s, 30s, 40s, 50s, or 60s; the leaching temperature is 20℃ to 50℃, for example, 20℃, 30℃, 40℃, or 50℃. This is beneficial for improving the leaching rate of transition metal elements.

[0053] S60: A lithium-rich solution is mixed with sodium carbonate and then evaporated and concentrated to obtain lithium carbonate.

[0054] Specifically, sodium carbonate powder can be added to a lithium-rich solution, and after evaporating and concentrating the lithium-rich solution, the concentrated liquid can be filtered to obtain lithium carbonate powder and sodium carbonate solution. The sodium carbonate solution can be reused in the evaporation and concentration process of the lithium-rich solution.

[0055] Pulse heating treatment (transient high-temperature heating technology) has the following beneficial effects:

[0056] (1) This application utilizes transient high-temperature heating technology induced by pulse current to treat waste cathode material powder and silicon dioxide powder. The electrothermal conversion efficiency is close to 100%. This heating method can heat the raw material from room temperature to 1000℃~3000℃ in a few seconds. The rapid heating and cooling characteristics can reduce the sintering or melting of waste cathode material powder, reduce the adhesion between carbon graphite boat and cathode material powder, improve the continuity of high-temperature heat treatment process, and improve the acid leaching extraction kinetics of transition metal elements.

[0057] (2) This application utilizes transient high-temperature heating technology to induce a rapid transformation of lithium components in waste cathode material powder from lattice lithium to lithium oxide vapor. At a transient high temperature of 800℃~1000℃ for 8min~14min, more than 50% of the lattice lithium in the waste cathode material powder can be converted into lithium oxide vapor. Specifically, according to Fick's diffusion law, L... i2O2 vapor initially undergoes chemisorption on the surface of SiO2 particles, followed by unreacted Li2O vapor migrating into the particle interior driven by the concentration gradient. Compared to traditional solid-phase calcination methods, the gas-phase reaction pathway exhibits higher reaction efficiency than the mass transfer efficiency at the solid-state interface, demonstrating significant advantages in chemical reaction kinetics. The waste cathode material powder and silica sheeting step proposed in this application effectively improves the problem of material separation after transient heat treatment. The lithium orthosilicate synthesized by the proposed process exhibits uniform lithium element distribution, and its CO2 adsorption performance is consistent with that obtained by solid-phase synthesis and commercially available lithium orthosilicate materials.

[0058] (3) This application utilizes transient high-temperature heating technology to induce the deoxygenation reduction of transition metal oxides in waste cathode material powder. Transient high-temperature heating reduces the valence of nickel, cobalt, and manganese in the cathode material to 0. These transition metal elements do not require the addition of hydrogen peroxide reducing agent in the subsequent acid leaching extraction process, and the thermodynamic trend of acid leaching is better than that of the original cathode material. In addition, the non-volatile lithium component is enriched on the surface of the cathode material particles in the form of lithium oxide, and 99% of the lithium can be leached out by water leaching at room temperature, realizing the full recovery of lithium components.

[0059] Reference Figure 1 The specific process flow for preparing lithium orthosilicate and lithium carbonate in this application includes the following steps:

[0060] (1) Place the waste lithium battery in NaCl salt water and soak it for 20 hours to fully discharge it, thereby reducing the safety hazards of combustion and explosion during the mechanical crushing process;

[0061] (2) The waste lithium batteries obtained in step (1) are placed in a vacuum drying oven and dried at 80°C. Then the waste lithium batteries are mechanically crushed to obtain crushed waste.

[0062] (3) Place the crushed waste obtained in step (2) into a vibrating screen and separate it by vibration to obtain the copper-aluminum current collector and plastic on the screen and the lithium battery black powder on the screen.

[0063] (4) The lithium battery black powder obtained in step (3) is placed in a foam flotation machine. After flotation separation, waste positive electrode material powder and waste graphite negative electrode are obtained.

[0064] (5) The waste positive electrode material obtained in step (4) is pressed under 15MPa pressure for 20s to obtain a positive electrode material sheet. The silicon dioxide powder is pressed under 15MPa pressure for 20s to obtain a silicon dioxide sheet. Then the positive electrode material sheet and the silicon dioxide sheet are placed in an electric heating graphite boat, with the silicon dioxide sheet stacked directly above the positive electrode material sheet. The material is subjected to transient high temperature heating to obtain lithium orthosilicate adsorbent material and lithium-rich transition metal powder.

[0065] (6) The lithium-rich transition metal powder obtained in step (5) is leached with deionized water and then filtered to separate the transition metal element and the lithium-rich solution.

[0066] (7) Add sodium carbonate powder to the lithium-rich solution obtained in step (6), evaporate and concentrate the lithium-rich solution, filter the concentrated liquid to obtain lithium carbonate powder and sodium carbonate solution.

[0067] The description of the various embodiments above tends to emphasize the differences between the various embodiments. The similarities or similarities between them can be referred to, and for the sake of brevity, they will not be repeated here.

[0068] The following specific embodiments illustrate the solution of this application. It should be noted that these embodiments are for illustrative purposes only and should not be considered as limiting the scope of this application. Where specific techniques or conditions are not specified in the embodiments, they are performed according to the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments whose manufacturers are not specified are all conventional products that can be obtained commercially.

[0069] Example 1

[0070] like Figure 1 As shown, a method for preparing CO2 adsorbent using waste lithium batteries includes the following steps:

[0071] (1) After discharging, crushing, screening, and flotation of the waste lithium cobalt oxide battery pack, 2g of waste positive electrode material powder is mixed with 0.4g of waste positive electrode material powder with a specific surface area of ​​400m². 2 / g of silicon dioxide powder was pressed into sheets at 15MPa pressure for 20s to obtain positive electrode material sheets and silicon dioxide sheets;

[0072] (2) Place the positive electrode material sheet in the electrothermal graphite boat, and stack the silicon dioxide sheet directly above the waste positive electrode material sheet. Set the pulse current parameters, where the current is 140A and the pulse time is 14min, and perform transient high-temperature heating treatment at a temperature of 1100℃ to obtain lithium orthosilicate adsorbent material and lithium-rich transition metal powder.

[0073] (3) Lithium-rich transition metal powder was extracted by water leaching. The liquid-to-solid ratio of the water leaching was 20:1, the water leaching temperature was 50℃, and the water leaching time was 10s. After water leaching, the solution was filtered to obtain lithium-rich solution and transition metal element.

[0074] (4) Add saturated sodium carbonate solution to lithium-rich solution, and obtain regenerated lithium carbonate after precipitation.

[0075] In this embodiment, the obtained lithium orthosilicate adsorbent material, after being heated to 625°C in a 15 vol% CO2 atmosphere, held at that temperature for 60 min, exhibited a maximum CO2 adsorption capacity of 0.33 g / g. After 20 adsorption-desorption cycles, the lithium orthosilicate adsorbent material maintained a stable CO2 adsorption capacity of 0.24 g / g. The overall lithium extraction rate of the entire process was 99.1%, and the purity of the obtained recycled lithium carbonate was 99.7%.

[0076] Example 2

[0077] The difference from Example 1 is as follows:

[0078] (1) After discharging, crushing, screening, and flotation of waste ternary lithium 811 battery packs, waste ternary lithium 721 battery packs, and waste ternary lithium 622 battery packs, 2g of mixed waste cathode material powder and 0.1g of material with a specific surface area of ​​100m² were added. 2 / g of silicon dioxide powder was pressed into sheets at 15MPa pressure for 20s to obtain positive electrode material sheets and silicon dioxide sheets;

[0079] (2) The pulse current is 100A, the pulse time is 8min, and the heating temperature is 900℃;

[0080] In this embodiment, the obtained lithium orthosilicate adsorbent material, after being heated to 625°C in a 15 vol% CO2 atmosphere, held at that temperature for 60 min, exhibited a maximum CO2 adsorption capacity of 0.28 g / g. After 20 adsorption-desorption cycles, the lithium orthosilicate adsorbent material maintained a stable CO2 adsorption capacity of 0.21 g / g. The overall lithium extraction rate of the entire process was 99.4%, and the purity of the obtained recycled lithium carbonate was 98.8%.

[0081] Example 3

[0082] The difference from Example 1 is as follows:

[0083] (1) Discharge, crush, screen and float together the waste ternary lithium 523 battery pack and the lithium cobalt oxide battery pack;

[0084] (2) The pulse current is 100A and the heating temperature is 900℃;

[0085] (3) The liquid-to-solid ratio of the water immersion is 10:1, the water immersion temperature is 20℃, and the water immersion time is 60s.

[0086] In this embodiment, the obtained lithium orthosilicate adsorbent material, after being heated to 625°C in a 15 vol% CO2 atmosphere, held at that temperature for 60 min, exhibited a maximum CO2 adsorption capacity of 0.26 g / g. After 20 adsorption-desorption cycles, the lithium orthosilicate adsorbent material maintained a stable CO2 adsorption capacity of 0.19 g / g. The overall lithium extraction rate of the entire process was 99.1%, and the purity of the obtained recycled lithium carbonate was 99.2%.

[0087] Example 4

[0088] The difference from Example 1 is as follows:

[0089] (1) Mix 2g of waste cathode material powder with 0.2g of material with a specific surface area of ​​200m² 2 / g of silica powder was compressed into tablets at 15MPa pressure for 20s;

[0090] (2) The pulse current is 120A, the pulse time is 10min, and the heating temperature is 1000℃;

[0091] (3) The liquid-to-solid ratio of the water immersion is 5:1, the water immersion temperature is 30℃, and the water immersion time is 30s.

[0092] In this embodiment, the obtained lithium orthosilicate adsorbent material, after being heated to 625°C in a 15 vol% CO2 atmosphere, held at that temperature for 60 min, exhibited a maximum CO2 adsorption capacity of 0.3 g / g. After 20 adsorption-desorption cycles, the lithium orthosilicate adsorbent material maintained a stable CO2 adsorption capacity of 0.21 g / g. The overall lithium extraction rate of the entire process was 99.2%, and the purity of the obtained recycled lithium carbonate was 99.1%.

[0093] Comparative Example 1

[0094] The difference from Example 1 is as follows:

[0095] (2) The positive electrode material sheet is stacked directly above the silicon dioxide sheet.

[0096] In this embodiment, the obtained lithium orthosilicate adsorbent material, after being heated to 625°C in a 15 vol% CO2 atmosphere, held at that temperature for 60 min, exhibited a maximum CO2 adsorption capacity of 0.09 g / g. After 20 adsorption-desorption cycles, the lithium orthosilicate adsorbent material maintained a stable CO2 adsorption capacity of 0.05 g / g. The overall lithium extraction rate of the entire process was 11.5%, and the purity of the obtained recycled lithium carbonate was 98.2%.

[0097] Comparative Example 2

[0098] The difference from Example 1 is as follows:

[0099] (2) Use a conventional resistance tube furnace for heating treatment.

[0100] In this embodiment, the obtained lithium orthosilicate adsorbent material, after being heated to 625°C in a 15 vol% CO2 atmosphere, held at that temperature for 60 min, exhibited a maximum CO2 adsorption capacity of 0.23 g / g. After 20 adsorption-desorption cycles, the lithium orthosilicate adsorbent material maintained a stable CO2 adsorption capacity of 0.17 g / g. The overall lithium extraction rate of the entire process was 78.3%, and the purity of the obtained recycled lithium carbonate was 97.1%.

[0101] It should be noted that this application is not limited to the above-described embodiments. The above embodiments are merely examples, and any embodiments with the same structure and effect as the technical concept within the scope of this application are included in the technical scope of this application. Furthermore, various modifications that can be conceived by those skilled in the art to the embodiments, and other ways of constructing by combining some of the constituent elements of the embodiments, without departing from the spirit of this application, are also included in the scope of this application.

Claims

1. A method for preparing lithium orthosilicate, characterized in that, include: Waste lithium batteries are discharged and pretreated to obtain waste cathode material powder. The waste cathode material powder is pressed into cathode material sheets; The positive electrode material sheet and the silicon dioxide sheet are stacked in an electrothermal graphite boat, wherein the silicon dioxide sheet is located on the side of the positive electrode material sheet away from the electrothermal graphite boat; The electrothermal graphite boat is subjected to pulse heating treatment at a temperature of 800℃~1000℃ to obtain the lithium orthosilicate.

2. The method according to claim 1, characterized in that, The waste lithium batteries include at least one of nickel-cobalt-manganese ternary lithium batteries and lithium cobalt oxide batteries; wherein the positive electrode active material of the nickel-cobalt-manganese ternary lithium batteries includes LiNi. 0.8 Co 0.1 Mn 0.1 O2, LiNi 0.7 Co 0.2 Mn 0.1 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.5 Co 0.2 Mn 0.3 At least one of O2.

3. The method according to claim 1 or 2, characterized in that, The method for preparing the silicon dioxide wafer includes: pressing silicon dioxide powder into a silicon dioxide wafer; wherein the specific surface area of ​​the silicon dioxide powder is 100 m². 2 / g~400m 2 / g.

4. The method according to claim 3, characterized in that, The mass ratio of the positive electrode material sheet to the silicon dioxide sheet is 1:(0.05~0.2).

5. The method according to claim 1 or 2, characterized in that, The pulse current of the pulse heating treatment is 100A to 140A, and the pulse time is 8min to 14min.

6. The method according to claim 1 or 2, characterized in that, The preprocessing includes: Waste lithium batteries that have undergone discharge treatment are mechanically crushed to obtain crushed waste materials; The crushed waste material is subjected to vibratory screening to obtain lithium battery black powder; The lithium battery black powder is subjected to foam flotation to obtain the waste cathode material powder.

7. An application of lithium orthosilicate in carbon dioxide adsorption, characterized in that, The lithium orthosilicate is prepared by the method described in any one of claims 1 to 6.

8. A method for preparing lithium carbonate, characterized in that, include: Waste lithium batteries are discharged and pretreated to obtain waste cathode material powder. The waste cathode material powder is pressed into cathode material sheets; The positive electrode material sheet and the silicon dioxide sheet are placed in an electrothermal graphite boat, wherein the silicon dioxide sheet is located on the side of the positive electrode material sheet away from the electrothermal graphite boat; The electrothermal graphite boat is subjected to pulse heating treatment at a temperature of 800℃~1000℃ to obtain lithium-rich transition metal powder. The lithium-rich transition metal powder is subjected to leaching treatment to obtain elemental transition metal and lithium-rich solution; The lithium-rich solution is mixed with sodium carbonate and then evaporated and concentrated to obtain the lithium carbonate.

9. The method according to claim 8, characterized in that, The leaching process includes mixing the lithium-rich transition metal powder with water, wherein the mass ratio of water to the lithium-rich transition metal powder is (5-20):

1.

10. The method according to claim 8 or 9, characterized in that, The leaching treatment time is 10s to 60s, and the leaching treatment temperature is 20℃ to 50℃.

Citation Information

Cited By

  • Process for synthesizing high-crystallinity lithium carbonate through photocatalysis-assisted carbonization of waste battery lixivium

    CN122144767A